TRANSFORMATION AND INNOVATION MANAGEMENT INCLUSIVE THROUGH UTILIZATION OF BIG DATA IN RESPONSIVE MODERN ORGANIZATION AND ADAPTIVE (Universitas Teknologi Muhammadiyah Jakarta (UTM Jakarta), 2025)
Digital transformation has brought significant changes in the way organizations manage data to enhance the effectiveness and inclusiveness of management. Big data has become one of the key factors in making more accurate, evidence-based, and inclusive decisions. This article examines how organizations can leverage big data to build more inclusive management systems through a descriptive qualitative approach. This research offers a model for the implementation of big data that includes strategies, advantages, obstacles, and solutions for its implementation in modern organizational environments. This research offers a big data implementation model that includes strategies, advantages, obstacles, and implementation solutions in modern organizational environments.